Dreptul la nume al autorului operelor de artă, literatură sau ştiinţă [Articol] - Chiroșca, Dorian (My University, 2005)
Author of the present article illustrates under the different aspects the important matters of the name right. The name right, as well as the paternity right, become evident simultaneously with creation of the work, however in contrast to the paternity right, the name right is realized simultaneously with publishing of the work. This becomes clear by the fact that up to the publication the work is not accessible to the public. According to the art. 9 of the Law on author right and relative rights of the Republic of Moldova, the author acquires the name right, that is the right to decide in what form shall appear his name in the procedure of evaluation of the work (with the proper name, pseudonym or anonym).